The Relation Between Demographic Factors and Craft Purchase Behavior of European Tourists in Isfahan - hamid zargham; banafsheh atrsaai (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2006)
The purpose aims tostudy the craft purchase behavior of European tourists in Isfahan and identify the determinants factors of this activity. lnthis study, tourists' purchase is based on the three- dimensional, conceptual model of Oh(2007). This model shows the relationship among demographic attributes, travel features, destination's environmental/ contextual characteristics and rourists' expenditure on handicrafts. The relation between the first three factors and tourists' expenditure on handicrafts in Isfahan has been analyzed via inferential statistics and the items of each of those variables have been ranked according to their relation with the expenditure. Tourists· craft purchase preferences have been prioritized using descriptive statistics and their expenditure has been ev aluated.